2003
DOI: 10.1046/j.1523-5378.2003.00122.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Application of 20 MHz Endosonography and Anti‐Helicobacter pylori Immunoblots to Predict Regression of Low‐grade Gastric MALToma by H. pylori Eradication

Abstract: Aim. We tested whether serial 20 MHz endosonography (EUS) and anti‐Helicobacter pylori immunoblots can predict the complete regression of gastric MALToma by H. pylori eradication. Methods. The serums of 17 MALToma patients, including 15 with low grade and two with high grade, were collected before therapy. Fifteen patients with low‐grade MALToma and 18 nonMALToma patients, all infected with H. pylori, have been followed with serum sampling, endoscopy, and EUS on enrollment, on the 2nd, 6th, and 12th months aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
15
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 22 publications
3
15
0
Order By: Relevance
“…The contradictory concept was further supported by our recent study, which showed that the negative seroconversion of anti‐ H. pylori immunoblots of FldA and CagA was not consistently followed by the complete regression of MALToma [8]. In our previous study, the serological responses to the small‐molecular‐weight proteins (SMWP) of H. pylori could be consistently converted as negative results after the tumor regression [8]. It is thus imperative to determine whether the SMWP of H. pylori could be related to the formation of MALT in gastric tissue.…”
mentioning
confidence: 90%
See 2 more Smart Citations
“…The contradictory concept was further supported by our recent study, which showed that the negative seroconversion of anti‐ H. pylori immunoblots of FldA and CagA was not consistently followed by the complete regression of MALToma [8]. In our previous study, the serological responses to the small‐molecular‐weight proteins (SMWP) of H. pylori could be consistently converted as negative results after the tumor regression [8]. It is thus imperative to determine whether the SMWP of H. pylori could be related to the formation of MALT in gastric tissue.…”
mentioning
confidence: 90%
“…However, whether the FldA and CagA could be significant virulent bacterial factors involved in the pathogenesis of MALT lymphoma remains a matter of debate, as contradictory data were also observed [12,13]. The contradictory concept was further supported by our recent study, which showed that the negative seroconversion of anti‐ H. pylori immunoblots of FldA and CagA was not consistently followed by the complete regression of MALToma [8]. In our previous study, the serological responses to the small‐molecular‐weight proteins (SMWP) of H. pylori could be consistently converted as negative results after the tumor regression [8].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The diverse outcomes after H. pylori infection are attributable to the H. pylori virulence factors, host genomic predisposition, and other environmental factors 7–9 . Nevertheless, successful H. pylori colonization is the leading step that links the host to risks of developing gastritis, peptic ulcer, gastric adenocarcinoma or MALToma 10–12 . As such, understanding the pathways of H. pylori colonization is important for selecting novel targets to prevent the development of H. pylori ‐related diseases.…”
Section: Introductionmentioning
confidence: 99%
“…H. pylori eradication is the initial treatment of choice in all gastric MALT The predictive value of EUS with respect to response to H. pylori eradication or radio-/chemotherapy is another challenge. In several studies using radial EUS or miniechoendoscopes a high predictive value has been shown [20][21][22][23][24][25][26] (Table 3). In all studies, a stage EI1 lymphoma was associated with a higher remission rate (up to 100%) as compared to lymphoma of stages EI2 and EII1.…”
mentioning
confidence: 98%